2013
DOI: 10.1179/1743294412y.0000000094
|View full text |Cite
|
Sign up to set email alerts
|

Arc enhanced laser melt injection WC particles on Al surface

Abstract: In order to overcome the difficulties of laser melt injection (LMI) on aluminium alloys, the process of tungsten inert gas (TIG) arc enhanced LMI ceramic particles was developed. The influence of process parameters, including laser power, TIG current, the direction of powder feeding, the carrier gas flow of powder and the shield gas flow of TIG, was investigated. The results have shown that to achieve appropriate surface enhancement effect, the powder should be fed from the back side of the laser beam. The dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…In the case of composite traces with SiC powder, the depth ratio of the grain penetration to that of the melting zone was unacceptably small and also melted SiC particles were observed—see Figure 3 . This is in accordance with our own experience and literature data, indicating that the fabrication of a composite layer of the Al-based alloy and SiC materials pair requires the substrate preheating to approximately 300 °C [ 14 , 17 , 23 , 24 ] or enhancement of the laser processing by the tungsten inert gas (TIG) arc method—a technique originally invented for the WC powder [ 28 ].…”
Section: Resultssupporting
confidence: 85%
“…In the case of composite traces with SiC powder, the depth ratio of the grain penetration to that of the melting zone was unacceptably small and also melted SiC particles were observed—see Figure 3 . This is in accordance with our own experience and literature data, indicating that the fabrication of a composite layer of the Al-based alloy and SiC materials pair requires the substrate preheating to approximately 300 °C [ 14 , 17 , 23 , 24 ] or enhancement of the laser processing by the tungsten inert gas (TIG) arc method—a technique originally invented for the WC powder [ 28 ].…”
Section: Resultssupporting
confidence: 85%
“…But the corrosion resistance of nitrided stainless steels is directly dependent on the nitriding process parameters like duration, nitriding atmosphere composition and the process temperature. The authors state, that the corrosion resistance of stainless steels is reduced at a plasma nitridation temperature above 450 °C (5), 460 °C for AISI 304 stainless steel (6), 475 °C (7) and 480 °C (8,9). Above this temperature occurs the iron and chromium nitrides precipitation (CrN) (8).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical and electrochemical properties of laser surface modified titanium alloy for biomedical applications were examined by Khosroshahi et al 13 They showed that the high value of microhardness was resulted, which could be attributed to grain refinement associated with laser melting and rapid solidification. Laser melt injection of WC particles on aluminium surface was studied by Li et al 14 They demonstrated that the powder should be fed from the back side of the laser beam to achieve appropriate surface enhancement effect and the depth of the melt layer increased first and, then, decreased with increasing laser power. Laser processing of TiC reinforced composite layer on Al-Si alloy surface was investigated by Viswanathan et al 15 The findings revealed that the layer was free from pores and TiC and Al-Si phases were almost uniformly distributed in the Ni-Al matrix.…”
Section: Introductionmentioning
confidence: 99%